The Effects of Combined Versus Single-Mode Resistance and Repeated Sprint Training on Physical Fitness, Hematological Parameters, and Plasma Volume Variations in Highly Trained Soccer Players - Abderraouf Ben Abderrahman; Ali Aloui; Nidhal Jebabli; Iyed Salhi; Jihen Khalfoun; Mohaned Omar; Cain C. T. Clark; Bogdan-Constantin Ungurean; Urs Granacher; Hassane Zouhal (Sports)
Objective: We examined the effects of eight weeks of single-mode resistance, repeated sprint training, and the combination of the two programs on selected measures of physical fitness (muscle power, speed, and body composition), hematological parameters, and plasma volume variations in highly trained soccer players. Sixty male soccer players from the Tunisian national Ligue were randomly allocated to a resistance training group (RTG), a repeated sprint training group (RSTG), a combined resistance and repeated sprint training group (CTG), or an active control group (CG, soccer training only). The training volumes were similar between groups. Before and after training, we examined body composition, squat jump (SJ), countermovement jump (CMJ), sprint 30 m (S30), repeated-sprint sequences (RSSs), hematocrit, hemoglobin, mean hemoglobin concentration (MHC), and plasma volume. Significant group-by-time interactions were recorded for the RSS indices, SJ, and S30 (p < 0.039], 0.1< ηp2 < 0.49]), as well as the hematological parameters (p = 0.0001–0.045, 0.11 < ηp2 < 0.46). In terms of physical fitness, using post hoc tests, the CTG showed significantly greater gains compared to the RSTG, RTG, and the CG on the best time index of the RSSs (p = 0.008; d = 4.1), SJ (p = 0.004; d = 4.18) and 30 m linear sprint time (p = 0.008; d = 3.84). Body fat percentage also decreased significantly in the CTG compared to all other groups (p < 0.005, 0.21 < d< 0.35). Regarding hematological parameters (i.e., hemoglobin and hematocrit), the CTG, RSTG, and RTG showed significant decreases (p < 0.05) in their hemoglobin and hematocrit values compared to the CG (p < 0.05, 0.11 < d< 2.22]). Eight weeks of combined training compared to single-mode training was found to be more effective in improving fitness measures in highly trained soccer players. However, there appeared to be no consensus regarding the effect of single and combined repeated-sprint and resistance training on the hematological system.